A policy-driven mental health and psychosocial support in African Union Peace Support Operations: the way forward in improving the psychosocial wellbeing of peace support personnel - Larry-Afutu, Joana Afful; Abotsi, Kenneth (Frontiers in Health Services, 2025)
BackgroundTo foster peace and security within Africa, the African Union Peace Support Operations (AUPSO) Division deploy personnel to volatile areas, predisposing them to physical and psychosocial problems. Though a lot is done to safeguard their physical health, their psychosocial problems have been relegated, predisposing them to mental health problems.AnalysisTo address these mental health and psychosocial problems, the African Union, in collaboration with Kofi Annan International Peacekeeping Training Centre, Ghana developed and implemented a Mental Health and Psychosocial Support (MHPSS) course for AUPSO personnel. Implementing MHPSS in mission areas is bedeviled with challenges, because there are no policy guidelines for MHPSS in PSOs.Policy optionsAt the behest of WHO's Action Plan 2013–2020 which encourages institutions and organizations to prioritize mental health of personnel, the United Nations adopted a mental health and well-being strategy to enhance the psychosocial wellbeing of its mission's personnel in 2018.ConclusionFeasibly, developing a MHPSS policy for PSOs would enhance the implementation of MHPSS programs in missionary areas to ensure that personnel are in a good psychosocial state to fulfil their missions’ mandate.